Identifikasi Akuifer Air Tanah di Desa Senawang, Kecamatan Orong Telu, Kabupaten Sumbawa Menggunakan Metode Geolistrik Schlumberger - Zakaria, Muhammad Faizal; Suyanto, Imam (Universitas Negeri Semarang, 2020)
Senawang District is an area in Sumbawa Province with a high level of drought. This study aims to provide additional information about groundwater to support the availability of clean water in Senawang District. The study used Geoelectric-Schlumberger Method as main method of subsurface identification. The acquisition was conducted with 10 points acquisition, with spacing between points is 200 m and the line stretch of 250 m. The results of data processing are a vertical resistivity variation in depth at each point measurement. This result will be interpreted into the type of rock and the presence of groundwater. The interpretation shows that the presence of groundwater aquifer with resistivity of 12.54 – 26.28 m, thickness 4.59 – 7.95 m, depth (upper part of the layer) 23.29 – 50.56 m. The type of groundwaters aquifer in the study area are confined aquifers.